Intracranial pseudoaneurysm after intracranial pressure monitor placement - Shah, Kushal J (BMJ Case Rep, 2014)
Traumatic intracranial pseudoaneurysms are a rare but severe complication following arterial injury. Pseudoaneurysm formation can occur secondary to blunt or penetrating trauma or iatrogenic injury. We report a case of traumatic pseudoaneurysm secondary to placement of an intracranial pressure (ICP) monitor. A 27-year-old man was involved in a motorcycle accident resulting in multiple intracranial hemorrhages. The patient underwent craniectomy and placement of an ICP monitor. 17 days later he developed dilation of his left pupil, with imaging demonstrating a new hemorrhage in the vicinity of the previous ICP monitor. A cerebral angiogram confirmed a left-sided distal M4 pseudoaneurysm which was treated by n-butyl cyanoacrylate embolization. Intracranial pseudoaneurysm formation following neurosurgical procedures is uncommon. Delayed intracranial hemorrhage in a region of prior intracranial manipulation, even following a procedure as ‘routine’ as placement of an ICP monitor, should raise the suspicion for this rare but potentially lethal complication.